PENINGKATAN KEKUATAN OTOT PADA PASIEN STROKE MENGGUNAKAN ROM: METODE CYLINDRICAL GRIP - Putra Agina Widyaswara Suwaryo; Siti Muslikhah; Barkah Waladani (AKPER Pemkab Purworejo, 2022)
Background: Stroke has become a health problem that is the main cause of disability and is one of the leading causes of death in the world. Stroke is the third leading cause of death after coronary heart disease and cancer in developing countries. Developing countries also accounted for 85.5% of the total deaths. One of the rehabilitation that can be given to stroke patients is range of motion exercises or commonly referred to as Range Of Motion. Cylindrical grip is part of the ROM. Cylindrical Grip is a functional hand exercise by holding a cylindrical object in the form of rolled tissue in the palm of the hand which functions to move the fingers to grip perfectly. Objective: to determine the effectiveness of Cylindrical Grip therapy in stroke patients. Method: research using literature study method or literature review with PICO analysis. Search using researchgate, sciencedirect, proquest and pubmed databases with keywords stroke, cylincrical grip, and muscle strength. Assessment of articles using Duffy's Research Appraisal Checklist Approach category of superior paper (score 205-306) Results: There were 10 articles that entered the superior paper, where all articles explained that ROM was effective in increasing muscle strength in stroke patients, and 2 articles using the cylindrical grip method were more effective than other. Conclusion: Cylindrical Grip ROM therapy is an effective alternative to increase muscle strength in stroke patients.